Fiscal management in federal democracies: Argentina and Brazil - Dillinger, William (1999)
In the 1980s, Argentina and Brazil faced similar problems, with subnational deficits adding to excess public deficits and high inflation. In the 1990s both countries continued with fiscal decentralization and with the struggle to bring about macroeconomic stability. At least up to 1998, Argentina had greater success, partly because the country imposed a harder budget constraint on the public sector at the national level and partly because it had stronger party control of the subnational governments and of the national legislators. For restraining local and state borrowing, getting the right incentives for subnational governments and particularly for their creditors proved more effective, in Argentina, than central government rules, in Brazil.